Probing the Microstructure in Pure Al & Cu Melts: Theory Meets Experiment - Song, Lin; Tian, Xuelei; Yang, Yanmei; Qin, Jingyu; Li, Hui; Lin, Xiaohang (Frontiers in Chemistry, 2020)
In present work, a new model of the atomic cluster structure is proposed to describe the structures of metallic melts, which is determined by metal Wulff construction with the crystal structure inside. The shapes of the structures are determined by surface energies of different crystal plane group, which are determined from density functional theory (DFT), and the size is given by the pair distribution function (PDF) of the experimental high-temperature X-ray diffraction (HTXRD). Using the Aluminum and Copper as the representative examples, we demonstrate that the simulated XRD curves from present models match the experimental results quite well, including not only the position and width of the peaks but also the relative intensity of the first and second peaks. These results indicate a successful model to describe the properties of metallic melts. At the same time, the model also explains a main peak deviation phenomenon between the XRD of metallic melt and the solid ones in pure metal Al. Finally, a picture of metallic melt is given, which is mainly composed of atomic cluster structures and free atoms around them.